Women on the move: Trafficking, sex work and reproductive health among West African migrant women - Sine Plambech; Maria Chiara Cerio (Danish Institute for International Studies (DIIS), 2021)
This report explores the interconnections between trafficking, sex work and reproductive health along the West African-European corridor. Fifty-one women were interviewed at different points of their journeys from Nigeria and Ivory Coast through Niger, Tunisia, Libya, across the Mediterranean to Italy and onwards to Northern Europe. Moving away from the do not migrate message, this project draws on migrant women's experiences to develop better harm reduction measures, with a special focus on reproductive health along the route. The argument that women are using 'anchor babies' to exploit humanitarian systems ignores how difficult it can be to reach Europe without getting pregnant, given the high level of sexual violence en route. Irregular migrant women face exclusion from reproductive healthcare and stress their need for assistance and information services. The report applies a trafficking-migration continuum to understand how categories of forced, voluntary or irregular migration will vary according to political and moral values. While often overlooked, debt plays a central role in the migratory experience. With the term indentured sex work migration, we switch the focus from human trafficking to a labour migration actively organised by women.
Keywords: 300; West Africa; migrant route; Europe; Denmark; Italy; sex work; pregnancy outcomes; violence en route; migrant women; trafficking